MODERN DIGITAL DENTISTRY: INNOVATIONS, APPLICATIONS, AND FUTURE DIRECTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Modern digital dentistry represents a paradigm shift in dental practice, integrating advanced technologies such as intraoral scanning, CAD/CAM systems, 3D printing, and artificial intelligence. These innovations have significantly improved diagnostic accuracy, treatment planning, and clinical outcomes. This paper reviews the key components of digital dentistry, its clinical applications, advantages, limitations, and future prospects.